The Impact of Health Promotion on Knowledge of Dental Caries Prevention in Elementary School Children - Ade Melia Rositian; Syamsulhuda Budi Musthofa; Nurjazuli (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Dental caries in children aged 5-9 years has 54% and 41.4% at age of 10-14 years in Indonesia. This is due to children's low awareness of dental and oral health. This research will discuss the impact of health promotion on knowledge of dental caries prevention in elementary schools. Review: The method of this research is a systematic literature review using PRISMA diagram with a total of 16 article. Conclusion: The results of data extraction in the 16 article known that there was a knowledge improvement through the pre-test and post-test process. This increase has an effect on children's insight into caries, so that it can increase children's willingness to brush their teeth regularly, reduce consumption of cariogenic foods and check with the dentist.